2006
DOI: 10.1016/s1726-4901(09)70195-9
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Hepatitis B and C in Type 2 Diabetic Patients

Abstract: The rate of seropositive anti-HCV is 2.8 times higher in type 2 DM patients than non-diabetic control subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
52
6
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 35 publications
11
52
6
5
Order By: Relevance
“…Therefore, we cannot establish the diabetic population as a group at high risk for HCV infection. Our findings did not confirm other studies that have reported increased HCV seroprevalence in patients with diabetes [10,[22][23][24][25][26] . In a case-control study conducted in the USA, 4.2% of 594 patients in a cohort with diabetes were found to be infected with HCV compared with 1.6% of control patients (377 patients with thyroid diseases) [27] .…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, we cannot establish the diabetic population as a group at high risk for HCV infection. Our findings did not confirm other studies that have reported increased HCV seroprevalence in patients with diabetes [10,[22][23][24][25][26] . In a case-control study conducted in the USA, 4.2% of 594 patients in a cohort with diabetes were found to be infected with HCV compared with 1.6% of control patients (377 patients with thyroid diseases) [27] .…”
Section: Discussioncontrasting
confidence: 99%
“…29 Nonalcoholic steatohepatits, a severe form of nonalcoholic fatty liver disease is regarded as an entity that can progress to cirrhosis 29 as well as primary liver cancers. 30,31 Moreover, type 2 diabetes is a risk factor of hepatitis C, 32 which can also progress to cirrhosis and hepatocellular carcinoma. 33 Additionally, type 2 diabetes has been found to be associated with insulin resistance, compensatory hyperinsulinemia 9,11 and elevated level of insulin-like growth factor, 11 which may interact with liver cells to stimulate mitogenesis and carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…measuring the prevalence of HCV markers among populations of diabetic patients [8,15,[25][26][27][28][29][30][31][32][33] . Most controlled studies have suggested a significant association, the proportion of HCV-positive persons among diabetics being two-to seven-fold compared to controls [8,15,29,32] . The prevalence of HCV markers among patients with T2D reported by uncontrolled studies was also claimed to be higher than that observed in the general population taken as a reference [25,27,30] .…”
Section: Association Between Hcv and T2dmentioning
confidence: 99%